Reproductive and sexual health in the Maldives: analysis of data from two cross-sectional surveys - Cockcroft Anne; Pearson LuWei; Hamel Candyce; Andersson Neil (BMC, 2011)
Abstract Background The Maldives faces challenges in the provision of health services to its population scattered across many small islands. The government commissioned two separate reproductive health surveys, in 1999 and 2004, to inform their efforts to improve reproductive and sexual health services. Methods A stratified random sample of islands provided the study base for a cluster survey in 1999 and a follow-up of the same clusters in 2004. In 1999 the household survey enquired about relevant knowledge, attitudes and practices and views and experience of available reproductive health services, with a focus on women aged 15-49 years. The 2004 household survey included some of the same questions as in 1999, and also sought views of men aged 15-64 years. A separate survey about sexual and reproductive health covered 1141 unmarried youth aged 15-24 years. Results There were 4087 household respondents in 1999 and 4102 in 2004. The contraceptive prevalence rate (CPR) for modern methods was 33% in 1999 and 34% in 2004. Antenatal care improved: more women in 2004 than in 1999 had at least four antenatal care visits (90.0% v 65.1%) and took iron supplements (86.7% v 49.6%) during their last pregnancy. The response rate for the youth survey was only 42% (varying from 100% in some islands to 12% in sites in the capital). The youth respondents had some knowledge gaps (one third did not know if people with HIV could look healthy and less than half thought condoms could protect against HIV), and some unhelpful attitudes about gender and reproductive health. Conclusions The two household surveys were commissioned as separate entities, with different priorities and data capture methods, rather than being undertaken as a specific research study. The direct comparisons we could make indicated an unchanged CPR and improvements in antenatal care, with the Maldives ahead of the South Asia region for antenatal care. The low response rate in the youth survey limited interpretation of the findings. But the survey highlighted areas requiring attention. Surveys not undertaken primarily for research purposes have important limitations but can provide useful information.